Plan integral de marketing para mejorar la visibilidad de la casa del maestro en el sector educativo del departamento del Atlántico (2024)
This document presents the design proposal for the comprehensive digital marketing plan for the La Casa del Maestro research center, to improve its visibility in the educational sector of the department of Atlántico. The company's problems, market analysis, methodology, objectives, and techniques used to carry out the user study through their social networks and identify which are real and which are potential in the demand for physical spaces are found in detail. for research, defining the strategies that must be applied to position the Casa del Maestro. The results obtained are presented based on monitoring the strategic matrix during the stipulated period of 2023 in the behavior of their social networks. In chapter I of the study, the deficiencies in the communication and advertising dissemination of the Casa del Maestro are analyzed, identifying the inadequate use of communication channels and the lack of others that could improve its visibility. A background check is carried out and an instrument is established to measure its recognition, finding that more than 80% of the surveyed population knows the Casa del Maestro and wishes to interact with it. Chapter II describes the applied research methodology, based on background information to find the best marketing strategy. Chapter III details the execution of the project and its results, showing a 30% increase in visibility on the selected platforms, which meets the expectations of the Casa del Maestro.